Romantiske stereotypier eller barnlige avvik. Arktis som oppdragende element i jentebøker fra 1940- og 1950-tallet - Karlsen, Silje Solheim (Nordlit, 2015)
Children’s literature has traditionally tended to be aimed primarily at raising and educating children. The setting has played an important role as a didactic and educational element, especially in literature for boys, where the natural setting has been pictured as a space of freedom without boundaries, following the pattern of the robinsonade. However, the didactic literature for girls was more related to the eighteenth-century genre of conduct literature, a British tradition aimed at giving girls and young women a sense of how they ought to behave, think, feel and respond, following conservative ideals of manners and morals. With this tradition in mind, it is quite interesting that many Norwegian books written for children and teens between the 1930s and 1970s take place in the Arctic, several of them with young girls as heroines and protagonists. Drawing on theories of the didactic function of children’s literature, focusing especially on the Arctic landscape as setting, this article examines three girls’ books from the period 1930–1950 and the roles and spaces this literature present as available for girls and young women. It addresses questions of the significance of the Arctic setting, and asks what kind of space these narratives offer and what kind of limitations and possibilities the representations contain.